Ohio boundary no. 2 : Map exhibiting the positions occupied on the Maumee Bay and river: viz: Turtle Island, the North Cape, and that above Toledo, together with the position of the "east line," in its passage of the Maumee River surveyed under the direction of Capt. Talcott, U.S. Engineers, by Lieuts. Hood & R.E. Lee. - Irwin, James R., d. 1848. ([U.S. Congress], 1835)
Map shows portion of the Maumee River south of Toledo, Ohio and portion of the North Cape of the Maumee in Maumee Bay in Lake Erie. Relief shown by hachures and land forms. Scale [1:12,000].